Connectivity and Food Security in 3T Villages in Eastern Indonesia: Community-Based Supply Chain Modeling - Intan Prasasti; Yulianah Yulianah; Ikram Febriansyah; Dian Rahmania; Ryan Hidayat; Jeki Chen (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to explore the role of regional connectivity in shaping food distribution dynamics and to develop a community-based food supply chain model to strengthen food security in disadvantaged, frontier, and outermost (3T) villages in Eastern Indonesia. Research Method: A descriptive qualitative approach with a case study design was employed. Data were collected through field observations, in-depth interviews, spatial analysis, review of secondary data, systems engineering techniques, and focus group discussions to refine the proposed model. Results and Discussion: The findings indicate that limited connectivity, dependence on external distribution channels, and inadequate storage infrastructure constrain food security in 3T areas. Based on these findings, this study proposes a Community-Based Supply Chain Model integrating BUMDes, Digital Village Granaries, Transportation Collectivity, and appropriate storage technologies to enhance local food system resilience. Implications: The study highlights the importance of combining infrastructure development with community institutions and context-sensitive technologies. Originality: This study offers an integrated framework linking regional connectivity, social capital, and local governance within a community-based food supply chain model tailored to 3T areas in Eastern Indonesia.